Study of the antimicrobial properties of Camellia sinensis in an oral microbial model - Banda, Alberto Figueroa (2018)
Objective: To determine the in vitro antibacterial effect of the extract of Camellia Sinensis (green tea) on an oral microflora model. Materials and methods: Two ethanolic green tea extracts of different origin (Peru and China) were used in concentrations of 16, 8, 4, 2, 1, 0.5 and 0.25mg / ml. The minimum and maximum inhibitory concentrations were evaluated on S. mutans, S. mitis, C. albicans, C. tropicalis, S. aureus, F. nucleatum, L. rhamnosus, L. casei, C. glabrata and E. faecalis strains. The obtained data were statistically analyzed using the Kruskal Wallis statistical test with a significance level of 5%. Results: C. sinensis showed a bacteriostatic effect for the strains of S. mutans, and fungistatic for C. albicans, C. tropicalis and C. glabrata. (P <0.05). Conclusion: The 16mg / ml ethanolic extract of Camellia Sinensis has an inhibitory effect on strains of S. mutans, C. albicans, C. tropicalis and C. glabrata.